-3=9+x

Simple and best practice solution for -3=9+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=9+x equation:


Simplifying
-3 = 9 + x

Solving
-3 = 9 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-3 + -1x = 9 + x + -1x

Combine like terms: x + -1x = 0
-3 + -1x = 9 + 0
-3 + -1x = 9

Add '3' to each side of the equation.
-3 + 3 + -1x = 9 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = 9 + 3
-1x = 9 + 3

Combine like terms: 9 + 3 = 12
-1x = 12

Divide each side by '-1'.
x = -12

Simplifying
x = -12

See similar equations:

| -3=9+8 | | y=8ln(5x) | | (-8)8= | | 5(2a-3)-6(a+2)=-7 | | x/8-12=-23 | | 8.95-21.35=X | | 11/3-2/3= | | 4v(2v+10v)=0 | | -4(y-3)+2(3y-5)=11 | | m=1/4;(0,-2) | | 3=-7m | | -29.2=1.7+5.8+5.3n | | 7x+14=3x-12 | | 36Ln(36t+1)=19 | | A(5)+b=192 | | -.2=x-2.76/.64 | | 2x^2/10^3-2x^2 | | 14-12=x | | 3ln(1/x) | | 3(x+2)-4=x+2x+2 | | F(x)=3x^2+7x-6 | | x^3=578 | | 7x+y=-10x+6 | | 56/x-4 | | 4k-7k=(-20)-1 | | 7.5/50=c | | 7x-14=3x-4 | | 0.7x-1.4=0.3 | | x(3x+14)=-8 | | 1250+92*p=7000 | | 3(3)-2(1)= | | 5+14.50p=64 |

Equations solver categories